Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1113/jphysiol.1978.sp012188
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and strontium concentration changes within skinned muscle preparations following a change in the external bathing solution.

Abstract: 1. A method for producing rapid [Ca2+] and [Sr2+] changes in the frog skinned muscle fibre preparation while maintaining constant all other cationic concentrations (Moisescu, 1976a, b) is described and analysed in detail. 2. Different experiments, some of them involving the Ca2+‐sensitive photoprotein aequorin, as well as theoretical considerations, indicate that with this method one can produce a Ca2+ (or Sr2+) concentration change within 0.1‐‐0.15 sec in a whole preparation having a diameter of 50 micrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
2

Year Published

1982
1982
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(135 citation statements)
references
References 26 publications
3
130
0
2
Order By: Relevance
“…The temperature regulating apparatus has been described previously (Moisescu & Thieleczek, 1978). The difference in temperature between solutions in any particular experiment did not exceed 0 5 0C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature regulating apparatus has been described previously (Moisescu & Thieleczek, 1978). The difference in temperature between solutions in any particular experiment did not exceed 0 5 0C.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental solutions were prepared using the techniques employed in this laboratory and apparent affinity constants which were previously determined (Ashley & Moisescu, 1977;Moisescu & Thieleczek, 1978Stephenson & Williams, 1981). All solutions contained physiological cations in physiological concentrations, the Ca2+ buffer EGTA, and caffeine and azide to reduce Ca2+ movements associated with the internal membranous systems; the sarcoplasmic reticulum and mitochondria.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the ability of the contractile apparatus to develop maximum Ca¥-activated force decreases only marginally for the duration of an experiment. Control experiments with three freshly dissected mechanically skinned muscle fibres activated successively by rapidly raising [Ca¥] to 4 ìÒ and then decreasing it to below 0·1 ìÒ (Moisescu, 1976;Moisescu & Thieleczek, 1978) have shown that the maximal Ca¥-activated force obtained at 30 ìÒ [Ca¥] decreased by only 6·6 ± 0·2 % after 35 activation-relaxation cycles lasting 4-6 s where the average force response was 85·5 ± 3·0 % of the maximum Ca¥-activated force. Both the duration of the activation and the force level attained during activation were considerably higher than the corresponding averages for the depolarization-induced force responses to 50% run-down.…”
Section: T_system Depolarization Experimentsmentioning
confidence: 99%
“…For the extracellular solutions, the 10 mÒ BAPTA was replaced by 8 mÒ EGTA and 2 mÒ EDTA (0 Mg¥ control solution) or 10 mÒ EGTA to which MgClµ was added to yield the free Mg¥ concentration indicated in the text. Free Mg¥ concentrations were determined from apparent affinity constants for EGTA, measured with the potentiometric method, with software kindly provided by R. Thieleczek (Moisescu & Thieleczek, 1978;Stephenson & Thieleczek, 1986). In all instances block was measured using whole-cell recordings of HEK 293 cells.…”
Section: Solutionsmentioning
confidence: 99%